Evaluasi Kualitas Tanah Sawah Intensif dan Sawah yang Dikonversikan untuk Kebun di Subak Kesiut Kerambitan Tabanan - ARTHAGAMA, I DEWA MADE; DANA, I MADE (Agrotrop : Journal on Agriculture Science; Vol 10 No 1 (2020)DO - 10.24843/AJoAS.2020.v10.i01.p01, 2020)
Evaluation Quality of Intensif Paddy Soils and Conversion Paddy Soils to Garden at Subak Kesiut Kerambitan Tabanan. This experiment conducted to evaluate intensif Paddy Soils and conversion paddy soils to garden at SubakKesiut Kerambitan Tabanan. There were two steps applied in this study including field survey to determine the research area and points soils sampling; analysis soils properties are: physic, chemistry and soils biology for get minimum data set to determine the soil quality at Laboratory of Soils and Enveronment Faculty of Agriculture Unud. The results of this study showed: the soil quality of intensif paddy soils is better than conversion paddy soils to garden, that showed with SQR at intensif paddy soil is 18 and at conversions paddy soil is 25. The limiting faktor at conversion paddy soils to garden is P available, there are less than at intensif paddy soils.